Machine learning and deep learning applications in sports biomechanical analysis: A systematic scoping review of performance enhancement and injury prevention strategies - Dhahbi, W.; Jebabli, N.; Boujabli, M.; Souaifi, M.; Dergaa, I.; Ezzdine, L. B. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
Aim: This scoping review systematically maps current trends in artificial intelligence applications for sports biomechanical analysis, examining performance enhancement and injury prevention utility, methodological approaches, implementation challenges, and ethical considerations.